Critical Analysis of Intzar Hussain’s Short Story “Kachway” - Dr. Khuram Aleem; Majid Mushtaq (Zaban-o-Adab, 2021)
"Kacheway" is a Symbolic short story of Intizar Hussain. This Short story has been narrated with the help of "JATAK KAHANIAN" Which relate to MAHATMA BUDH birth and life. The mythology which extract from Buddha’s philosophy is based on this very short story. The Metamorphosis’ of a human being as depicted in this story a human being in ancient ages as well as in contemporary period is the main theme of this Story. This article helps us to understand the symbolic aspects of this piece of prose.